Effect of the presence of pinned particles on the structural parameters of a liquid and correlation between structure and dynamics at the local level - Patel, Palak; Bhattacharyya, Sarika Maitra (Journal of Chemical Physics, 2024)
Pinning particles at the equilibrium configuration of the liquid is expected not to affect the structure and any property that depends on the structure while slowing down the dynamics. This leads to a breakdown of the structure dynamics correlation. Here, we calculate two structural quantities: the pair excess entropy, S-2, and the mean field caging potential, the inverse of which is our structural order parameter (SOP). We show that when the pinned particles are treated the same way as the mobile particles, both S-2 and SOP of the mobile particles remain the same as those of the unpinned system, and the structure dynamics correlation decreases with an increase in pinning density, ``c.'' However, when we treat the pinned particles as a different species, even if we consider that the structure does not change, the expression of S-2 and SOP changes. The microscopic expressions show that the interaction between a pinned particle and a mobile particle affects S-2 and SOP more than the interaction between two mobile particles. We show that a similar effect is also present in the calculation of the excess entropy and is the primary reason for the well-known vanishing of the configurational entropy at high temperatures. We further show that, contrary to the common belief, the pinning process does change the structure. When these two effects are considered, both S-2 and SOP decrease with an increase in ``c,'' and the correlation between the structural parameters and the dynamics continues even for higher values of ``c.''